2012
DOI: 10.3109/14767058.2012.663835
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of maternal immunization against influenza: the critical role of obstetricians

Abstract: Two years after the recommendation of influenza immunization during pregnancy, most post-partum women recalled being neither recommended nor adequately informed about influenza vaccine and its safety. This identifies major gaps in awareness and/or communication in healthcare workers and suggests that improving immunization safety/efficacy awareness among obstetricians as the most likely method to improve flu immunization during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
75
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 31 publications
15
75
1
1
Order By: Relevance
“…Despite the extensive research behind vaccine safety, physician concern regarding these results is not new, nor is it limited to the obstetricians. [11][12] Others in our study believed that pertussis vaccine does not need to be administered in the office because the patients would receive Tdap vaccine in the post-partum unit after delivery, revealing the need for more education as to the importance of maternal immunization to optimally protect the newborn from infection through passively delivered transplacental antibodies. Even more interestingly, some of our surveyed providers stated a lack of need to administer pertussis vaccine due to low incidence of pertussis infection in New York State.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite the extensive research behind vaccine safety, physician concern regarding these results is not new, nor is it limited to the obstetricians. [11][12] Others in our study believed that pertussis vaccine does not need to be administered in the office because the patients would receive Tdap vaccine in the post-partum unit after delivery, revealing the need for more education as to the importance of maternal immunization to optimally protect the newborn from infection through passively delivered transplacental antibodies. Even more interestingly, some of our surveyed providers stated a lack of need to administer pertussis vaccine due to low incidence of pertussis infection in New York State.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies have shown that provider recommendation of influenza vaccine for pregnant women is strongly associated with increased vaccine uptake in this population. [8][9][10][11][12] However, few studies describe obstetric provider attitudes toward pertussis vaccination in pregnant women. In this study, we aimed to describe vaccine attitudes and practices of obstetrical providers in New York State following the ACIP recommendation for pertussis vaccination in women in the third trimester of each pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found overwhelming evidence on the need for provider recommendation to facilitate pregnant women's immunization decision-making. 14,[17][18][19][20] Yet, provider recommendation results from effective continuing medical education provided by ACOG and others on the need for immunization during pregnancy. This model suggests a need for more evidence-based information about vaccine safety and immunogenicity profiles as well as neonatal protection directed to providers who, in turn, will be able to recommend immunization to women for whom contraindication does not exist.…”
mentioning
confidence: 99%
“…99 Similarly, lack of recommendation from an obstetric provider appears to be a strong predictor of not receiving indicated maternal vaccines. 98 These findings underscore the importance of a strong and direct provider recommendation of indicated vaccines during pregnancy. Providers should talk directly to patients about recommended vaccinations.…”
Section: Maximize Conveniencementioning
confidence: 96%
“…90 Recommend Verbal, face to face communication from a physician appears to be an overwhelmingly powerful motivator of vaccine acceptance in pregnancy. 67,98 In one recent study of postpartum women in Delaware, those who recalled a specific recommendation from a healthcare provider about influenza vaccination were 3 times more likely to be vaccinated than those who did not report a healthcare provider recommendation. 70 In a similar study in Australia with overall lower influenza vaccine coverage of participants (25%), women who reported receiving provider recommendation of influenza vaccination were 41 times more likely to have received antepartum vaccination.…”
Section: Maximize Conveniencementioning
confidence: 99%